Pneumococcal disease prevention among adults: Strategies for the use of pneumococcal vaccines. (27th November 2015) - Pilishvili, Tamara; Bennett, Nancy M.
Abstract: Use of the pneumococcal conjugate vaccines among children in the US since 2000 has dramatically reduced pneumococcal disease burden among adults. Significant vaccine-preventable morbidity and mortality from pneumococcal infections still remains, especially among older adults. The US Advisory Committee on Immunization Practices (ACIP) has recently recommended the routine use of both pneumococcal conjugate (PCV13) and polysaccharide vaccines (PPSV23) for adults ≥65 years. These recommendations were based on the remaining burden of illness among adults and the importance of non-bacteremic pneumonia prevention in light of new evidence confirming the efficacy of PCV13 to prevent pneumococcal pneumonia among older adults. This paper reviews the evidence that led the ACIP to make recommendations for PCV13 and PPSV23 use among adults, and highlights potential gaps to be addressed by future studies to inform adult vaccination policy. The changing epidemiology of invasive pneumococcal disease and pneumonia should be closely monitored to evaluate the effectiveness and continued utility of the current vaccination strategy, and to identify future directions for pneumococcal disease prevention among older adults.